2007
DOI: 10.1186/1471-2458-7-51
|View full text |Cite
|
Sign up to set email alerts
|

Higher prevalence of smoking and lower BMI, waist circumference, cholesterol and triacylglyceride levels in Prague's homeless compared to a majority of the Czech population

Abstract: Background: Homeless people have higher morbidity and mortality rates than the general population. Research has shown that cardiovascular disease is the leading cause of death in older homeless adults. This study was undertaken to describe the prevalence of cardiovascular risk factors in the homeless population in Prague.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…Several studies have investigated the cardiovascular risk profile in homeless and socially deprived individuals (Kim et al 2008;Kubisova et al 2007; Lee et al 2005;Szerlip and Szerlip 2002). A high prevalence of hypertension and smoking among the homeless compared with the general population was found, whereas the prevalence of hyperlipidemia, elevated BMI, and obesity were lower among the homeless.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have investigated the cardiovascular risk profile in homeless and socially deprived individuals (Kim et al 2008;Kubisova et al 2007; Lee et al 2005;Szerlip and Szerlip 2002). A high prevalence of hypertension and smoking among the homeless compared with the general population was found, whereas the prevalence of hyperlipidemia, elevated BMI, and obesity were lower among the homeless.…”
Section: Introductionmentioning
confidence: 95%
“…Studies which have attempted to determine the food and nutrient intake of the homeless can be categorised into those using either questionnaire, interview or biochemical assessment methods as outlined in Table 1 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) . These have provided an insight into the diets of homeless individuals but must be interpreted in light of the inherent methodological limitations of each technique.…”
Section: Homelessness and Nutrient Intakementioning
confidence: 99%
“…The demonstration of reduced total cholesterol and TAG levels in the Prague homeless community (6) , a finding in contrast to increased dietary saturated fat and serum cholesterol in American homeless (17) , was considered by the researchers to reflect such differences between the two countries (6) . The demonstration of reduced total cholesterol and TAG levels in the Prague homeless community (6) , a finding in contrast to increased dietary saturated fat and serum cholesterol in American homeless (17) , was considered by the researchers to reflect such differences between the two countries (6) .…”
Section: Limitations Of Research Into the Nutrient Intake Of The Homementioning
confidence: 99%
“…Results from the Prague homeless population are very similar. The authors found the prevalence of smoking to be significantly higher among homeless men (93%) and women (83%) compared to the general Czech population, men 38% and women 35% (33). A Slovak study implemented in an asylum home showed that 89.4% of 226 homeless people were smokers while 60.6% of them consumed too much alcohol (34).…”
Section: Smokingmentioning
confidence: 99%